2019
DOI: 10.32604/cmes.2019.06858
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Ratio and Residual Approaches in the Homotopy Analysis Method and Some Applications in Nonlinear Science and Engineering

Abstract: A ratio approach based on the simple ratio test associated with the terms of homotopy series was proposed by the author in the previous publications. It was shown in the latter through various comparative physical models that the ratio approach of identifying the range of the convergence control parameter and also an optimal value for it in the homotopy analysis method is a promising alternative to the classically used h-level curves or to the minimizing the residual (squared) error. A mathematical analysis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We consider the following additional boundary conditions which lead the solution of the Eqs. ( 22)- (24) as…”
Section: Original Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the following additional boundary conditions which lead the solution of the Eqs. ( 22)- (24) as…”
Section: Original Functionsmentioning
confidence: 99%
“…However, there are some nonlinear situations that do not have a perturbation quantity like HAM [17,18], HPM [19], OHAM [20] and ADM [21]. Similarly some further updated versions of the aforementioned methods have been applied to study various problems in fluid mechanics, we refer few as [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Platt (1961) gave the concept of bioconvection. The most relevant studies have been reported by Bhatti et al (2021), Khan et al (2017), Turkyilmazoglu (2019, 2022), Balla et al (2020), Khan and Makinde (2014) and Khan et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…EOF is simulated by Chang and Tsao (2007). Few staple investigations on different non-Newtonian fluid models can be seen in Das and Chakraborty (2006), Zhao et al (2008), Zhao and Yang (2011), Zhao and Yang (2012), Zhao and Yang (2013b), Berli and Olivares (2008), Berli (2010), Turkyilmazoglu (2022), Othman et al (2019), Riaz et al (2021a), Zhang et al (2021), Goodarzi et al (2020), Turkyilmazoglu (2019), Saffarian et al (2020), Ellahi et al (2019), Awan et al (2022), Ellahi (2013) and Elelamy et al (2020); however, a hybrid model for non-Newtonian fluids in the said studies is more general form of the Carreau non-Newtonian model. At low and intermediate shear rate, a Carreau fluid behaves as a Newtonian and power law fluid, respectively (Alqarni et al , 2022; Riaz and Sadiq, 2020; Nabwey et al , 2022a; Jalali et al , 2020).…”
Section: Introductionmentioning
confidence: 99%